2021
DOI: 10.1186/s13073-021-00992-x
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of methicillin-resistant Staphylococcus aureus (MRSA) lineage replacement in China

Abstract: Background Methicillin-resistant Staphylococcus aureus (MRSA) is a major nosocomial pathogen subdivided into lineages termed sequence types (STs). Since the 1950s, successive waves of STs have appeared and replaced previously dominant lineages. One such event has been occurring in China since 2013, with community-associated (CA-MRSA) strains including ST59 largely replacing the previously dominant healthcare-associated (HA-MRSA) ST239. We previously showed that ST59 isolates tend to have a comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
40
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 94 publications
1
40
1
Order By: Relevance
“…It is also possible that other low-frequency clones have started to increase in frequency during this time, competing with the dominant lineages albeit still undetected. Local clonal expansion followed by replacement of contemporary lineages was previously reported in S. aureus ST239 by STs 5 and 228 in Hungary ( 38 ) and by ST59 in China ( 39 ). We did not find evidence of replacement by rare genotypes from our data set; however, this may be due to the sampling strategies used in our data set that that could have introduced biases in characterization of common and rare lineages.…”
Section: Discussionmentioning
confidence: 67%
“…It is also possible that other low-frequency clones have started to increase in frequency during this time, competing with the dominant lineages albeit still undetected. Local clonal expansion followed by replacement of contemporary lineages was previously reported in S. aureus ST239 by STs 5 and 228 in Hungary ( 38 ) and by ST59 in China ( 39 ). We did not find evidence of replacement by rare genotypes from our data set; however, this may be due to the sampling strategies used in our data set that that could have introduced biases in characterization of common and rare lineages.…”
Section: Discussionmentioning
confidence: 67%
“…A recent study indicated that the ongoing replacement of ST239 by ST59 in China, is probably due to the carriage of the chp gene that enhances ST59 virulence activity. 25 Up now, the transmission success of ST59 clones in hospital settings remains unclear. Jin et al suggested that clonal transmission was putatively associated with the intrinsic physiological properties of ST59, rather than with its resistance to antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…Since the emergence and epidemic spread of USA300 (CC8) clone in the early 2000s (30, 71, 72), CA-lineages have dominated infection surveillance studies (19, 71, 72). CA-lineages are typically thought to carry larger -more cumbersome, and less resistant -SCC mec types I, II and III, and often carry toxin genes such as the PVL genes.…”
Section: Discussionmentioning
confidence: 99%
“…Hypervirulent pandemic clonal lineages have helped spread S. aureus around the world and the geographic distribution of many lineages is dynamic, with different lineages dominating infections in specific global regions (18, 19). Waves of MRSA lineages have risen and been replaced since the emergence of MRSA in the 1940s (18, 20).…”
Section: Introductionmentioning
confidence: 99%